2016
DOI: 10.1002/jsfa.7882
|View full text |Cite
|
Sign up to set email alerts
|

Fermented goat milk improves antioxidant status and protects from oxidative damage to biomolecules during anemia recovery

Abstract: Fermented goat milk consumption induces a protective increase in TAS together with lower oxidative damage biomarkers, revealing that the milk protects main cell bioconstituents (lipids, protein, DNA, prostaglandins) from evoked oxidative damage during anemia recovery. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 41 publications
0
18
1
2
Order By: Relevance
“…44,45 Our research group has previously reported that fermented goat milk induces a significant elevation of some antioxidant endogenous enzymes, together with an increase in TAS, a decrease in 8-hydroxy-2 ′ -deoxyguanosine, reducing DNA strand breaks, hydroperoxides, 15-F2t-isoprostanes and protein carbonyl groups in tissues, revealing an improvement in both systemic and cellular antioxidant activity of plasma and tissues due to fermented goat milk consumption. 16 This protective antioxidant effect in the tissues, increasing TAS and decreasing the oxidative damage biomarkers, which directly correlates with the expression/activity of antioxidant enzymes, could explain why fermented goat milk reduces CTGF plasma levels, reducing the cardiovascular risk during anemia recovery.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…44,45 Our research group has previously reported that fermented goat milk induces a significant elevation of some antioxidant endogenous enzymes, together with an increase in TAS, a decrease in 8-hydroxy-2 ′ -deoxyguanosine, reducing DNA strand breaks, hydroperoxides, 15-F2t-isoprostanes and protein carbonyl groups in tissues, revealing an improvement in both systemic and cellular antioxidant activity of plasma and tissues due to fermented goat milk consumption. 16 This protective antioxidant effect in the tissues, increasing TAS and decreasing the oxidative damage biomarkers, which directly correlates with the expression/activity of antioxidant enzymes, could explain why fermented goat milk reduces CTGF plasma levels, reducing the cardiovascular risk during anemia recovery.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in VEGF, SICAM‐1, sE‐selectin, and MCP‐1 recorded with fermented goat milk can be attributed to the beneficial nutritional character of this type of milk, which provides a lower substrate for lipid peroxidation and consequently decreases the generation of free radicals and monocyte migration and adhesion. Additionally, the ability of fermented goat milk peptides to inhibit deleterious changes caused by lipid oxidation appears to be related to certain amino acid residues in the peptides, such as tyrosine, methionine, histidine, lysine, and tryptophan, which are capable of chelating pro‐oxidative metal, inhibiting lipid oxidation, reducing hydroperoxides output and contributing to the improvement in TAS, limiting oxidative damage to the biomolecules, including blood‐vessel walls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been reported that oxidative damage results in amyloid deposition in the brain, resulting in neuronal cell death and neurodegenerative diseases [47,48]. In this sense, we have previously reported [49,50] that fermented goat milk increased some antioxidant enzymes in brain tissue as well as total antioxidant status and melatonin, even in the case of Fe overload. These increases limit the oxidative damage to the brain biomolecules (lipids, protein DNA, prostaglandins) and protect the nervous tissue of the oxidative-induced cell death that induces neurodegenerative processes.…”
Section: Discussionmentioning
confidence: 77%
“…Pretreatment with FCM prevented oxidative damage induced by CCl 4 in the renal tissue and accompanied by a decrease in the levels of MDA and PCO. This could be due to beneficial nutritional characteristics of fermented milk which provide a lower substrate for lipid peroxidation and consequently decreases the generation of free radicals (Moreno-Fernandez et al 2017). Fardet & Rock (2017) reported that fermented milk may inhibit oxidative stress, especially due to the production of antioxidant peptides.…”
Section: Discussionmentioning
confidence: 99%